Assessing the effectiveness of problem-based and lecture-based learning environments on students' achievements in electronic works. Issue 4 (October 2018) - Orji, Chibueze Tobias; Ogbuanya, Theresa Chinyere
The purpose of this study was to investigate the effectiveness of problem-based and lecture-based learning environments on students' achievement in electronic works. The design was randomized subjects with pretest and posttest control group design. The participants ( N = 148) were randomized to treatment and control conditions. Repeated measures analysis of variance and univariate analysis of variance were conducted by the researchers to compare changes across the treatment and control group participants. To test for differences in categorical data representing characteristics of the participants, the researchers used Chi-square (χ 2 ) statistic. Results show that the experimental group achieved higher achievement scores than the control group for electronic works achievement test at the posttest and follow-up test stages. Furthermore, the study found that there was no significant difference ( P > 0.05) in the achievement of students in the different ability levels and genders after the treatment. Hence, problem-based learning was advocated for teachers of electronic works in Nigeria.